Generalized relative entropies in the classical limit - Kowalski, Andres Mauricio (2015)
Our protagonists are (i) the Cressie-Read family of divergences (characterized by the parameter γ), (ii) Tsallis' generalized relative entropies (characterized by the q one), and, as a particular instance of both, (iii) the Kullback-Leibler (KL) relative entropy. In their normalized versions, we ascertain the equivalence between (i) and (ii). Additionally, we employ these three entropic quantifiers in order to provide a statistical investigation of the classical limit of a semiclassical model, whose properties are well known from a purely dynamic viewpoint. This places us in a good position to assess the appropriateness of our statistical quantifiers for describing involved systems. We compare the behaviour of (i), (ii), and (iii) as one proceeds towards the classical limit. We determine optimal ranges for γ and/or q. It is shown the Tsallis-quantifier is better than KL's for 1.5